Conservation of plant genetic resources by cryopreservation - Chin, Hoong Fong (Yayasan Sabah/Innoprise Corporation and Sabah Museum, 2001)
In the conservation of biodiversity, hundreds of animal and plant species have been successfully cryopreserved. Plants alone account for over 200 species of which 70 species are tropical plants. Cryopreservation is one of the more recent techniques which is used in ex-situ conservation as a complementary. method to in vitro genebanks. Recently, a number of seed banks in advanced countries have cryopreserved orthodox seeds for long term storage of plant genetic resources. Many tropical plants are difficult to conserve such as timber, fruit and plantation crops because they produce recalcitrant seeds and their clones are vegetatively propagated. They are commonly conserved in field and in vitro genebanks. This is where cryopreservation of plant tissues, embryos, meristems and pollen can playa major role in in vitro conservation. Presently no single method will be enough to conserve plant genetic diversity; a holistic approach has to be adopted.mAdvances in cryopreservation techniques have been rapid in the last decade. Development of simplified procedures in cryopreservation will provide greater potential and broader applicability for long term storage of plant genetic resources. In future such novel techniques will be more widely used even in developing countries. In this paper, the present status and constraints in conservation of several priority species using cryogenic storage are described. Future studies, development activities and public awareness of such techniques to develop cryogenic conservation are recommended and discussed.